Exploring the characteristics and drivers of indirect energy consumption of urban and rural households from a sectoral perspective. Issue 5 (20th June 2020) - Li, Xin; He, Xiaoqiong; Luo, Xiyu; Cui, Xiandan; Wang, Minxi
Abstract: China is actively taking measures to guide the household energy‐saving consumption pattern because the total household indirect energy consumption and CO2 emissions have rapidly multiplied from 2002 to 2017 with an annual growth rate of 5.95%, and 5.56%, respectively. This paper calculates indirect energy consumption and CO2 emissions by four energy sources (raw coal, crude oil, natural gas, and electricity), analyzes the energy structure, and conducts a structural decomposition analysis in urban and rural areas in China from 2002 to 2017. The results reveal that the indirect energy consumption and CO2 emissions of urban households was 3.84 and 3.80 times, respectively, that of rural households in 2017 with most contributions from the 'Agriculture, Forestry, Animal Husbandry, and Fishery', 'Foods and Tobacco', and 'OTHERS' sectors. The energy consumption structure has changed. The percentage of coal consumption falls from 66.87% to 57.62%. Electricity consumption, ranked second, increased substantially from 10.77% to 22.90%. The key sectors of the energy mix have been found to help energy conservation. The high indirect energy consumption sectors with higher indirect energy intensity are the key sectors, especially the 'Processing of Petroleum, Coking and Processing of Nuclear Fuel' and 'Production and Supply of Electric Power and Heat Power'. The consumption structure effect is more obvious in urban areas than in rural areas. In the process of urbanization, its effect has little impact on urban indirect energy consumption. It implies that the focus is on optimizing consumption structure rather than reducing consumption scale. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd.